Diálogo y Sexualidad integral en los estudiantes de décimo año de Educación general básica - Guaraca Silva, Katherine Paola (2024)
This research aimed to diagnose dialogue and integral sexuality in tenth-grade students of General Basic Education. The research had a quantitative approach. It had a descriptive scope. Therefore, it was a diagnostic research. Its population consisted of 12 students enrolled in tenth grade. Using the survey technique and the structured questionnaire as an instrument was essential. This research showed that communication at home is limited to education and collaboration in household chores. In addition, the vision of comprehensive sexuality is limited because it is limited to the body and methods of pregnancy prevention, leaving aside the emotional development for a healthy couple relationship. They do not receive medical advice on the changes of adolescence. Parents develop a vertical relationship based on their authority as adults; consequently, the dialogue regarding sexuality is limited to warnings about respecting their bodies. This study concludes that tenth-grade students do not dialogue at home about appropriate loving relationships or sexual maturity. It was also possible to identify limitations in the conceptualization and practice of comprehensive sexuality. However, teenagers recognize the importance of establishing loving relationships based on respect